Effect of plant protein isolates on the structural – mechanical properties of wheat dough - Makhynko, Valeriy; Drobot, Vira; Holikova, Tatiana (My University, 2017)
The results of using isolates of soya, pea and rice flour as well as of dry wheat gluten in the making of bread dough have been presented. Taking into account the high water absorption capacity of these products, effect of the protein isolates on the structural-mechanical properties of the dough has been investigated. On the basis of farinogram curves the additional quantity of water needed to obtain proper structure of dough made from all types of raw materials has been determined. A formula of calculation the additional quantity of water has been proposed. It proves that most quantity of water is needed for dough with isolate of soya protein – 2.3 g per 1 g of added isolate. Isolate of pea protein needs additionally 1.5 g of water, dry wheat gluten – 1.3 g, and isolate of rice protein – 0.9 g of water. The proposed calculation has been checked for mixes with different proportion of raw materials and its effectiveness has been proven. The calculation method was used to determine the additional quantity of water required to obtain wheat dough with necessary structural and mechanical properties.
Keywords: soya; pea; rice; gluten; Farinograph; protein isolate; water absorption; соя; горох; рис; клейковина; фаринограф; білковий ізолят; водопоглинання; белковый изолят; водопоглощение; кафедра технології хлібопекарських і кондитерських виробів; кафедра готельно-ресторанної справи